Institutional Degeneration and the Economic Crisis in Spain. (November 2014) - Royo, Sebastián
The economic crisis has had an earth-shattering effect in Spain at all levels: economic, political, institutional, and social. There are different interpretations about the causes of the crisis. Most of the analyses on the economic crisis in Spain have concerned themselves with phenomena like mismanaged banks, excessive debts, the bubble in the real estate sector, or the loss of competitiveness. Others have sought to explain the crisis as a byproduct of European Monetary Union integration. This article moves beyond those explanations and argues that a fundamental reason for the crisis is rooted in the process of institutional degeneration that preceded the crisis.